EVALUASI KINERJA KEBIJAKAN KESEHATAN IBU DAN ANAK (Studi Evaluasi Policy Output dan Policy Outcome Program Expanding Maternal and Neonatal Survival (EMAS) di Kabupaten Sidoarjo) - Nurul Jamila Hariani, 071311133045 (FAKULTAS ILMU SOSIAL DAN ILMU POLITIK, 2017)
This study aims to evaluate the performance and the factors that affected the performance of Expanding Maternal and Neonatal Survival (EMAS) program in Sidoarjo. The EMAS Program is a project of the Indonesian government in cooperation with USAID. In hope, this program could be replicated independently by the regions. Sidoarjo is one of several intervention areas of the EMAS program in East Java that was selected to be a pilot district. But, after the program ends, Sidoarjo didn’t continue this program. Therefore, it is necessary to evaluate the program's performance to know how far the program can achieve the desired objectives. This research employed qualitative research method. Data collection was conducted using observation, in-depth interviews, and documentary. The informants were selected by purposive method and continued by snowball method. This study finds that the performance of the EMAS Program in Sidoarjo is good enough. This is because, from seven indicators of policy output (access, bias, coverage, frequency, service provision, accountability, suitability of the program with the target groups), six indicators have been achieved. While, one indicator, called coverage, had not been achieved. In addition, the indicators of policy outcomes (initial, intermediate and long-term outcomes), have been achieved. This research also finds the factors that most affect the performance of the program are the resources, disposition and the communication between organizations and implementers. This study recommends the government of Sidoarjo to continue the EMAS program using independent financial resources. Although MMR and IMR haven’t decreased significantly in the last 5 years, the outcomes can increase the community participation in improving the quality of maternal and neonatal services.